Promoting knowledge sharing in academic environments using non-monetary factors. Issue 8 (27th October 2017) - Dezdar, Shahin
Abstract : Purpose: Knowledge sharing is very important in non-profit organizations such as academic institutes and universities. This research is a laudable attempt in this vital area to collaborate, refine and advance knowledge production endeavours in universities. The purpose of this study is to formulate a theoretical framework to investigate the non-monetary factors that encourage knowledge-sharing behaviour among postgraduate students. Design/methodology/approach: A field survey was conducted among postgraduate students in Iranian public universities to obtain empirical evidence. Structural equation modelling was used to analyse the collected data. Findings: The results revealed that knowledge-sharing behaviour is influenced by humility, interpersonal trust, reputation, self-efficacy and enjoyment of helping others. Originality/value: Most of the prior studies focussed on rewards and monetary incentive factors to encourage knowledge sharing, whereas this paper examines the non-monetary factors that increase the willingness to share knowledge.